Acute and Delayed Effects of Stress Eliciting Post-Traumatic Stress-Like Disorder Differentially Alters Fecal Microbiota Composition in a Male Mouse Model - Hoke, Allison; Chakraborty, Nabarun; Gautam, Aarti; Hammamieh, Rasha; Jett, Marti (Frontiers in Cellular and Infection Microbiology, 2022)
The association between the shift in fecal resident microbiome and social conflicts with long-term consequences on psychological plasticity, such as the development of post-traumatic stress disorder (PTSD), is yet to be comprehended. We developed an aggressor-exposed (Agg-E) social stress (SS) mouse model to mimic warzone-like conflicts, where random life-threatening interactions took place between naïve intruder mice and aggressive resident mice. Gradually these Agg-E mice developed distinct characteristics simulating PTSD-like aspects, whereas the control mice not exposed to Agg-E SS demonstrated distinct phenotypes. To further investigate the role of Agg-E SS on the resident microbiome, 16S rRNA gene sequencing was assayed using fecal samples collected at pre-, during, and post-SS time points. A time agonist shift in the fecal microbial composition of Agg-E mice in contrast to its controls suggested a persistent impact of Agg-E SS on resident microbiota. At the taxonomic level, Agg-E SS caused a significant shift in the time-resolved ratios of Firmicutes and Bacteroidetes abundance. Furthermore, Agg-E SS caused diverging shifts in the relative abundances of Verrucomicrobia and Actinobacteria. An in silico estimation of genomic potential identified a potentially perturbed cluster of bioenergetic networks, which became increasingly enriched with time since the termination of Agg-E SS. Supported by a growing number of studies, our results indicated the roles of the microbiome in a wide range of phenotypes that could mimic the comorbidities of PTSD, which would be directly influenced by energy deficiency. Together, the present work suggested the fecal microbiome as a potential tool to manage long-term effects of social conflicts, including the management of PTSD.